Penggunaan Metode Kooperatif Picture And Picture Guna Meningkatkan Kualitas Pembelajaran - Suryani Suryani (Tanjungpura University, 2019)
In the teaching and learning process of Social Sciences, many problems are carried out by the teacher. One of them is some students still rely on their teacher's activities in learning, so the role of students is still very lacking. Even thought, the teacher always involving students to play an active in learning process. In contrary, students assume that the subject of Social Sciences is very boring. So that this causes a low quality of learning in Social Sciences, especially in SMP Negeri 21 Pontianak. This cases has tickled the writer to take the theme of research on picture and picture cooperative methods to improve the quality of learning and increase the interest and activity of students in teaching and learning activities in Social Sciences.As for the techniques used of data collection is through observation by teachers and collaborators. The research involved two cycles of 42 students. While the data analysis used description with percentage techniques. Furthermore the level of activity of students and teachers is expressed in the category of